Estudo da interação entre metais e nanoestruturas de carbono por primeiros princípios - Sabrina Silva Carara (2010)
In the present work, we investigate the structural and electronic properties of based carbon nanostructures and metallic elements, by first-principles methods, based in the Density-Functional Theory. The studied nanostructures in that work are: lattices of thiolcoveredgold nanoparticles deposited on graphene layers and graphene bilayers, (10,0) zigzag carbon nanotubes compressed by gold or C-diamond surfaces, and Ni/Fe/graphene metallic heterostructures. In the case of nanoparticles lattices on graphene, we investigate the modifications on the eletronic states of graphene when a triangular lattice of (covered or not) Au nanoparticles deposited on a graphene layer. A similar study have been done for Au nanoparticles deposited on graphene bilayers to four possible stacking configurations. In the case of zigzag nanotubes, we explore the semiconductor-metal transition of (10,0) tube inducedby radial compression of Au(111) or C-diamond(111) surfaces. The necessary force that should be applied to occur the transition was estimed as well as the value of force constant of the nanotube by unity of tube's lenght. For the last, we performed a theorethical study of the structural, electronic and magnetic properties of the metallic heterostructures Ni(111)/Fe(111)/graphene and Ni(111)/Fe(110)/ graphene. Interplane distances, formation energy of the heterostructures and spin magnetic moments of the Ni, Fe and C atoms. In a general way, we found modications in the electronic structure of the studied carbonnanostructures for all cases when these nanostructures interact with metals.